2016
DOI: 10.1177/0954405415619871
|View full text |Cite
|
Sign up to set email alerts
|

Tool condition monitoring system based on support vector machine and differential evolution optimization

Abstract: A tool condition monitoring system based on support vector machine and differential evolution is proposed in this article. In this system, support vector machine is used to realize the mapping between the extracted features and the tool wear states. At the same time, two important parameters of the support vector machine which are called penalty parameter C and kernel parameter [Formula: see text] are optimized simultaneously based on differential evolution algorithm. In order to verify the effectiveness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Due to the complexity of tool wear during machining process, the establishment of tool wear mechanism models is more and more challenging, while data-driven methods can learn data-driven models from a large volume of data, and the data-driven model can be equivalent to complex mechanism models within certain range of error, so data-driven method provides a new idea for accurate tool wear prediction. 1318…”
Section: Related Workmentioning
confidence: 99%
“…Due to the complexity of tool wear during machining process, the establishment of tool wear mechanism models is more and more challenging, while data-driven methods can learn data-driven models from a large volume of data, and the data-driven model can be equivalent to complex mechanism models within certain range of error, so data-driven method provides a new idea for accurate tool wear prediction. 1318…”
Section: Related Workmentioning
confidence: 99%
“…Multi-classes classification model in the first stage is used to diagnose whether the part is printed normally with specific relative temperature parameters inputting. therefore, what the multi-classes classification model based on SVM (Debnath et al , 2004; Wang et al , 2017; Xu et al , 2018) in the first stage is going to solve is a binary classification problem.…”
Section: Multi-classes Classification Modelingmentioning
confidence: 99%
“…Xu et al (2020) developed a hybrid method by combining an adaptive neuro fuzzy inference system and vibration based communication particle swarm optimization and predicted tool wear in machining of compacted graphite iron. Wang et al (2017) developed a SVM based TCM system and predicted tool life using cutting force signals collected at different tool wear states in milling of titanium alloy. Venkatarao and Murthy (2018) predicted surface roughness and tool vibration using ANN, RSM and SVM and reported that the SVM predicted the tool vibration and surface roughness with good accuracy than ANN and RSM.…”
Section: Introductionmentioning
confidence: 99%